2016
DOI: 10.1016/j.ijantimicag.2015.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic combination therapy can select for broad-spectrum multidrug resistance in Pseudomonas aeruginosa

Abstract: Combination therapy with several antibiotics is one strategy that has been applied in order to limit the spread of antimicrobial resistance. We compared the de novo evolution of resistance during combination therapy with the β-lactam ceftazidime and the fluoroquinolone ciprofloxacin with the resistance evolved after single-drug exposure. Combination therapy selected for mutants that displayed broad-spectrum resistance, and a major resistance mechanism was mutational inactivation of the repressor gene mexR that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 30 publications
3
59
0
2
Order By: Relevance
“…There are, however, several other genes involved in resistance to beta-lactam antibiotics (36, 37) that did not show mutations in this study. The dacB mutations observed at low frequencies during the development of resistance to ceftazidime influence the expression of AmpC beta-lactamases (38). The ampD mutations observed after the growth of cells made resistant to ceftazidime in antibiotic-free medium fulfill a role in peptidoglycan synthesis (39).…”
Section: Discussionmentioning
confidence: 99%
“…There are, however, several other genes involved in resistance to beta-lactam antibiotics (36, 37) that did not show mutations in this study. The dacB mutations observed at low frequencies during the development of resistance to ceftazidime influence the expression of AmpC beta-lactamases (38). The ampD mutations observed after the growth of cells made resistant to ceftazidime in antibiotic-free medium fulfill a role in peptidoglycan synthesis (39).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been reported that combination antibiotics may select for broad-spectrum multi-drug resistance, at least in P. aeruginosa where dysregulated efflux pumps appear to drive high levels of resistance following ciprofloxacin (fluoroquinolone) and ceftazidime (β-lactam) treatment [79]. Hence, further evaluation of drug combinations will be necessary to inform any decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…Tulathromycin and tildipirosin are in the same class of antimicrobials and have similar mechanisms of action. Bacterial pre-exposure to antimicrobials has been implicated as an important risk factor for AMR evolution during subsequent antimicrobial treatments [24,27,28]. Recently, the effect of sequential antimicrobial treatments on the development of antimicrobial resistance has been demonstrated for Pseudomonas aeruginosa and Klebsiella pneumonia in-vitro.…”
Section: Resultsmentioning
confidence: 99%